Management Strategies of Vestibular Neuritis:- A Review - Santosh Kumar Swain; Chappity Preetam (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
A common peripheral vestibular disorder called vestibular neuritis (VN) results in abrupt development of vertigo symptoms without any accompanying auditory symptoms, such as tinnitus, aural fullness, or hearing impairment. The precise cause of VN is yet unknown. The clinical history and test results serve as the foundation for the VN diagnostic criteria. Despite an unclear cause of VN, a thorough understanding of its clinical course and management has been established. Clinically, VN is characterized by a spinning sensation that lasts longer than 24 hours, the absence of cochlear symptoms, and other neurological symptoms. The diagnosis of VN is done by different tests which include a head impulse test, bithermal caloric test, and vestibular-evoked myogenic potential tests. The treatment of VN is based on different stages of this disease such as acute, subacute, and chronic. Antiemetics, vestibular suppressants, and intravenous hydration are some of the symptomatic treatments available. For those with chronic VN, vestibular rehabilitation is a highly useful tool in lowering feelings of lightheadedness and floating. The usefulness of antivertigo medications for VN is not well shown. The purpose of this review article was to explore the current management strategies of VN.